Map of North America - Thomas, Cowperthwait & Co. (Thomas, Cowperthwait & Co., 1850)
This map shows all of North America and the surrounding area. Each of the countries is shaded in color and labeled. Major cities and some states and provinces in the U.S., Mexico, and Canada are labeled, but not all delineated. Bodies of water and geographic features are marked (with relief shown by hachures). Prime meridian: Washington.